'Almost bled to death' : the effects of the Anglo Boer War on societal transformation in the Orange River Colony (Historia, 2021)
Paul Kennedy suggests that it was in times of war that the early European state took on its obviously modern features. 'It was war' Kennedy writes, 'and the consequences of war', that provided a much more urgent and continuous pressure toward 'nation building than ... philosophical considerations and slowly evolving social tendencies'. Charles Tilly puts it even more succinctly : "War made the state and the state made war".
Keywords: War; European state; nation building; philosophical considerations; social tendencies